2005
DOI: 10.1037/0736-9735.22.4.508
|View full text |Cite
|
Sign up to set email alerts
|

Construct validation of the Rorschach Reality-Fantasy Scale in alexithymia.

Abstract: The study applies Winnicott's conceptualization of potential space to the alexithymia construct by using a new Rorschach index, the Reality-Fantasy Scale (RFS). The scale uses variables derived from the Rorschach Comprehensive System (Exner, 2000, 2001) to detect different types of psychopathological manifestations conceptualized as forms of collapse of potential space. Following previous research, the present study further evaluates the construct validity of the RFS in a sample of 92 patients with inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 49 publications
0
23
1
5
Order By: Relevance
“…The principal findings of these authors regarding alexithymia within the Rorschach include -Pure F% (proportion of responses based only on the external contours of the blot) was the Comprehensive System variable with the largest effect size (r = .70 in Porcelli & Meyer, 2002) and has been noted in several studies (Acklin & Alexander, 1988;Bash, 1986;Tibon et al, 2005). As Porcelli and Meyer pointed out (2002), research data reviewed by Exner (2003) and Weiner (1998) has indicated that this variable is closely associated with a defensive lack of engagement, concrete and simplistic thinking styles, narrowing of the perceptual field, and a coping style marked by the avoidance of complexity, featuring restricted and stereotypical ideation.…”
Section: Assessment: Comparing the Rorschach Comprehensive System Andmentioning
confidence: 95%
See 3 more Smart Citations
“…The principal findings of these authors regarding alexithymia within the Rorschach include -Pure F% (proportion of responses based only on the external contours of the blot) was the Comprehensive System variable with the largest effect size (r = .70 in Porcelli & Meyer, 2002) and has been noted in several studies (Acklin & Alexander, 1988;Bash, 1986;Tibon et al, 2005). As Porcelli and Meyer pointed out (2002), research data reviewed by Exner (2003) and Weiner (1998) has indicated that this variable is closely associated with a defensive lack of engagement, concrete and simplistic thinking styles, narrowing of the perceptual field, and a coping style marked by the avoidance of complexity, featuring restricted and stereotypical ideation.…”
Section: Assessment: Comparing the Rorschach Comprehensive System Andmentioning
confidence: 95%
“…4. The current working method for Rorschach clinicians from the Parisian School (Boucherat-Hue, 2002;Chabert, 1988;Debray, 1983;de Tychey, 2004;Gueniche et al, 2008;Roman, 1997) is not carried out within the same research perspective as most American studies on the subject (Acklin & Alexander, 1988;Lumley et al, 2007;Porcelli & Meyer, 2002;Sultan & Porcelli, 2006;Tibon, Weinberger, Handelzalts, & Porcelli, 2005). Indeed, American clinicians are prone to carry out comparative studies on alexithymia and allied disorders within larger groups using both the Rorschach and self-report questionnaires in which inferential statistical analyses are often employed.…”
Section: Assessment: Comparing the Rorschach Comprehensive System Andmentioning
confidence: 95%
See 2 more Smart Citations
“…More recently, Porcelli and Meyer (2002) furthered this line of Rorschach research and demonstrated that alexithymic participants (as identified by self-report) were more likely to show an impoverished fantasy life, poorly adapted emotional expression, poor coping resources, concrete and stereotypical thinking, and social conformity with compromised relationships. Tibon, Weinberger, Handelzalts, and Porcelli (2005) also explored the "collapse of potential space" on the Rorschach using a new reality-fantasy index and found modest, positive associations of this index with self-reports of alexithymia.…”
Section: The Assessment Of Alexithymiamentioning
confidence: 99%